Pengetahuan Konseptual Matematis Siswa - Fad, Nur (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Conceptual knowledge is basic knowledge that connects pieces of information such as facts, skills, concepts, or principles. Knowledge can be understood deeply if someone masters a comprehensive understanding of the concept. This study aims to analyze the importance of mathematical conceptual understanding in mathematics learning. This study was conducted using the literature review method, namely by conducting a systematic review of relevant literature sources in scientific journals, books and academic articles about the importance of conceptual knowledge on students' mathematics learning outcomes. The indicators of students' mathematical conceptual understanding are: students verbally restate the concepts that have been learned, students classify objects based on whether or not the requirements to form the concept are met, students apply concepts algorithmically, students present concepts in various forms of mathematical representation, and students relate various concepts (internal and external mathematics). Based on the research conducted, it was found that conceptual knowledge plays an important role in the teaching and learning process and is the basis for achieving the final results. The reason why mathematical conceptual understanding is important for students is as a basis for knowledge that is the goal of early mathematics learning. If the basic concept received by students is wrong, it is difficult to correct it, especially if it has been applied in solving mathematics problems